A novel front in sustainable microbial management: computational analysis of curcumin and mangiferin’s synergistic action against Bacillus anthracis - Perveen, Kahkashan; Bukhari, Najat A.; Alshaikh, Najla A.; Kondaveeti, Suresh Babu; Alsulami, Jamilah A.; Debnath, Sandip; Kumarasamy, Vinoth (Frontiers in Microbiology, 2024)
Background Microorganisms are crucial in our ecosystem, offering diverse functions and adaptability. The UNGA Science Summit has underscored the importance of understanding microbes in alignment with the UN Sustainable Development Goals. Bacillus anthracis poses significant challenges among various microorganisms due to its harmful effects on both soil and public health. Our study employed computational techniques to investigate the inhibitory effects of curcumin and mangiferin on Bacillus anthracis, with the aim of presenting a novel bio-based approach to microbial management. Methods Employing high-throughput screening, we identified potential binding sites on B. anthracis. Molecular docking revealed that curcumin and mangiferin, when synergistically combined, exhibited strong binding affinities at different sites on the bacterium. Our findings demonstrated a significant drop in binding free energy, indicating a stronger interaction when these compounds were used together. Findings Results of Molecular docking indicated binding energies of −8.45 kcal/mol for mangiferin, −7.68 kcal/mol for curcumin, and a notably higher binding energy of −19.47 kcal/mol for the combination of mangiferin and curcumin with CapD protein. Molecular dynamics simulations further validated these interactions, demonstrating increased stability and structural changes in the bacterium. Conclusion This study highlights the effectiveness of natural compounds like curcumin and mangiferin in microbial management, especially against challenging pathogens like B. anthracis. It emphasizes the potential of sustainable, nature-based solutions and calls for further empirical research to expand upon these findings.